Prevalence of Extraglandular Manifestations in Patients With Primary Sjögren’s Syndrome in Southern Norway: A Comparison to the Literature - Lars JORKJEND; Anders JOHANSSON; Ann Katrin JOHANSSON (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate the prevalence of extraglandular manifestations (EGM) in a group of Norwegian patients suffering from primary Sjögren’s syndrome (pSS) and compare these findings with the literature. Material and methods: Fifty-three female patients (mean age 60±11.6 years; range 33 to 85 years) fulfilling the clinical criteria for pSS were included in the study. To investigate the prevalence of EGM, a PubMed search from April 1976 to August 2012 identified 100 relevant publications by 88 authors, comprising a total of 14,861 pSS patients. An attempt was made to compare the obtained results regarding the prevalence of EGM with our results. Results: In our study group, mean prevalence rate of EGM was 42.1% with a range from 0 to 92.5% compared to the range of 0.8 to 94% in the PubMed reports on EGM. Epidemiological studies involving large groups of patients tend to yield lower prevalence of EGM than studies based on a smaller sample size. We were unable to compare the reports of prevalence of EGM in patients with pSS due to different methodologies and classification criteria applied in the different studies. Conclusion: The prevalence of pSS in this study was within the range of that reported in the literature. Due to methodological issues, we were unable to compare reports of prevalence of EGM in pSS. Our findings suggest that studies including larger sample sizes may be subjected to underreporting.